Struktur Komunitas dan Persentase Tutupan Kanopi Mangrove di Pantai Keranji, Desa Paremas, Lombok Timur - Puna, Salvina Herawaty; Sahrani, Putri; Tirayya, Nadia Hulwa; Buhari, Nurliah; Damayanti, Ayu Adhita; Lestariningsih, Wiwid Andriyani; Rahman, Ibadur (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2024)
Mangroves are coastal ecosystems rich in biodiversity and play a crucial role both globally as carbon sinks and locally in maintaining ecological balance and providing habitats for various species. Understanding the structure of mangrove communities is essential, as it involves studying the components and interactions within the environment. This research aims to examine the community structure and canopy cover percentage of mangroves at Keranji Beach, Paremas Village, East Lombok. Mangrove data were collected using the line transect method, while canopy cover data were obtained using hemispherical photography. The study identified 7 mangrove species i.e: Sonneratia alba, Avicennia alba, Avicennia marina, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, and Bruguiera gymnorrhiza. The density of the mangrove ecosystem at the tree and sapling levels falls within the very dense category (≥1500 individuals/ha). S. alba was the species with the highest importance value index (INP) (231% - 271%), indicating its significant role and contribution to the mangrove community. For the seedling category, two mangrove species were found, R. apiculata and B. gymnorrhiza, each with a 1% presence. The average percentage of mangrove canopy cover was 64.8%, classified as moderate with a good rating.